Play time : Jacques Tati and comedic modernism - Turvey, Malcolm, 1969- (Film and culture., 2020)
"Jacques Tati is viewed as one of the most innovative filmmakers in the history of cinema. At the same time, he also achieved global box-office success and a devoted following. In drawing on and subverting the conventions of film comedy, Tati not only satirized aspects of modern life, he attempted to develop in his viewers a playful, participatory attitude toward the modern world in order to overcome what he saw as a passivity characteristic of modernity. Malcolm Turvey argues that Tati captured both an elite and a popular audience by combining a modernist aesthetic with slapstick, sight gags, and other popular traditions of comedian-centered comedy that had developed in the silent era. In discussing films such as Play Time, Mon Oncle, and Mr. Hulot's Holiday, Turvey describes Tati's distinct comedic sensibility as one that was 'democratic' in allowing the viewer to choose what to look at in a particular scene. In addition to considering Tati's distinct comedic style, Turvey also considers the director's satirical view of the bourgeoisie and his love/hate relationship with modernity. Amply illustrated with images from the Tati's films, Play Time provides an illuminating and in-depth understanding of the richness of Tati's work"--Publisher's description